Z‐Thickness Blending: Effective Fragment Merging for Multi‐Fragment Rendering - Kim, Dongjoon; Kye, Heewon (Computer graphics forum, 2021)
An effective fragment merging technique is presented in this study that addresses multi‐fragment problems, including fragment overflow and z‐fighting, and provides visual effects that are beneficial for various screen‐space rendering algorithms. The proposed method merges locally adjacent fragments along the viewing direction to resolve the aforementioned problems based on cost‐effective multi‐layer representation and coplanar blending. We introduce a z‐thickness model based on the radiosity spreading from the viewing z‐direction. Moreover, we present the fragment‐merging schemes and rules for determining the visibility of the merged fragments based on the proposed z‐thickness model. The proposed method is targeted at multi‐fragment rendering that handles individual fragments (e.g., k‐buffer) instead of representing the fragments as an approximated transmittance function. In addition, our method provides a smooth visibility transition across overlapping fragments, resulting in visual advantages in various visualization applications. In this paper, we demonstrate the advantages of the proposed method through several screen‐space rendering applications.